Geology expedition to Todzha - Oydup, Choyganmaa K. (The New Research of Tuva, 2010)
A report on expedition of a group of scientists from the Tuvan Institute of Integrated Exploration of Natural Resources of the Siberian Branch of Russian Academy of Sciences and Institute of Geology and Mineralogy of the Siberian Branch of Russian Academy of Sciences to the Todzha district of Tuva. Notes about the difficulties of the fieldwork life of a scientist.
Keywords: Tuvan Institute of Integrated Exploration of Natural Resources of the Siberian Branch of Russian Academy of Sciences; fieldwork; expedition; impressions; Todzha; topography; geology